Intellectual property in Ukraine under martial law: legal regulation, administrative and civil aspect - Leheza, Yevhen; Yerofieienko, Larysa; Komashko, Volodymyr (DIXI, 2023)
The purpose of the research is legal regulation of intellectual property in Ukraine under martial law. It has been established that proper public administration of the intellectual property portfolio under the conditions of martial law in Ukraine is particularly relevant to avoid problems with potential court cases in the future. It is also substantiated that the preservation of data is relevant for protection and enforcement of intellectual property rights in Ukraine in the post-war economy. The following methods were used in the research: analysis of biographical sources, synthesis, deduction, comparative analysis, meta-analysis, etc. The article emphasizes that the state enterprise Ukrpatent, which fulfills the powers of the National Intellectual Property Authority in the field of intellectual property, continues to work in the conditions of a full-scale war of the Russian Federation against Ukraine, while ensuring the relevant functions and continuous operation of the state system of intellectual property legal protection. As a result, it was established, based on the analysis of data from Ukrpatent, that the number of registered objects of industrial property in Ukraine for the first half of 2023 compared to the first half of 2022 is 74.7%, which indicates a good result for wartime.